2021
DOI: 10.1101/2021.05.23.445128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local structure-function relationships in human brain networks across the lifespan

Abstract: The human connectome is the set of physical pathways linking brain regions to one another. Empirical and in silico studies have demonstrated that the structure of this network helps shape patterns of functional coupling between brain regions. To better understand this link between structure and function, a growing number of studies have derived geometric, dynamic, and topological predictors from structural connectivity in order to make predictions about correlation structure. These studies, however, have typic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 144 publications
3
38
0
Order By: Relevance
“…This observation is in line with previous studies demonstrating that shortest paths matrices are relatively poor predictors of static resting FC compared to matrices based on diffusion or other decentralized processes, e.g. communicability [1315, 25, 26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in line with previous studies demonstrating that shortest paths matrices are relatively poor predictors of static resting FC compared to matrices based on diffusion or other decentralized processes, e.g. communicability [1315, 25, 26].…”
Section: Discussionsupporting
confidence: 92%
“…Model fitness is typically defined ad hoc and the differences in performances between models – if model comparison is even performed – is often small [26]. Second, until recently [26, 27], communication models have been applied exclusively at the whole-brain level, i.e. the modeling framework assumes that every pair of brain regions communicates using the same policy.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, the authors showed increases in structurefunction coupling, particularly in transmodal cortices [3]. Another recent study showed consistent findings that the correspondence of structural and functional networks is preserved in transmodal regions across the adult lifespan, while sensorimotor systems showed a decreasing trend of structurefunction coupling [39]. In the current work, we built on this growing literature to assess how adolescent changes in multiscale cortical wiring are associated with changes in brain network function.…”
Section: Introductionmentioning
confidence: 52%
“…A growing body of evidence supports that CMs can explain a greater portion of variation in FC than SC alone. Previous studies along these lines have focussed mostly on the global scale [30, 31]—FC between regions pairs across the whole brain—and local scale [62, 63]—FC profiles of individual regions. Here, we add to this literature by considering how network communication models can uncover mesoscopic relationships between brain structure and function.…”
Section: Discussionmentioning
confidence: 99%